Exploring the Factors Contributing to the High Ultimate pH of Broiler Pectoralis Major Muscles Affected by Wooden Breast Condition - Baldi, Giulia; Yen, Con-Ning; Daughtry, Morgan R.; Bodmer, Jocelyn; Bowker, Brian C.; Zhuang, Hong; Petracci, Massimiliano; Gerrard, David E. (Frontiers in Physiology, 2020)
The elevated ultimate pH (pHu) found in Wooden Breast (WB) meat suggests an altered muscular energetic status in WB but also could be related to a prematurely terminated post-mortem pH decline. The aim of this study was to explore the factors contributing to the elevated pHu and establish whether the occurrence of WB defect alters muscle post-mortem carbohydrate metabolism and determine if the contractile apparatus reflects such changes. A total of twenty-four carcasses from Ross 308 male chickens were obtained from a commercial producer and harvested using commercial processing procedures. Carcasses were categorized into unaffected (NORM) and WB groups (n=12 each) and samples were collected from cranial bone-in Pectoralis major (PM) muscles at 15 min and 24 h post-mortem for the determination of pH, glycolytic metabolites, adenonucleotides, buffering capacity, phosphofructokinase (PFK) activity, and in vitro pH decline. Twenty-four additional deboned PM samples (12 NORM and 12 WB) were collected from the same processing plant to assess muscle histology and sarcomere length at four different locations throughout the PM muscle. Data show that the reduced glycolytic potential of WB muscles only partially explains the higher (P<0.001) pHu of WB meat, as residual glycogen along with unaltered PFK activity suggest that neither glycogen nor a deficiency of PFK are responsible for arresting glycolysis prematurely. The dramatic reduction in ATP concentrations in the early post-mortem period suggests a defective ATP-generating pathway that might be responsible for the reduced pH decline in WB samples. Further, the addition of excess of ATPase extended post-mortem glycolysis of WB meat in an in vitro glycolytic system. WB-affected samples have longer (P<0.001) sarcomeres compared to NORM, indicating that the existence of compromised energy-generating pathways in myopathic muscles that may have had consequences on the muscle contraction and tension development, as in vivo, also during the post-mortem period. Considering the overall reduced glycolytic potential and the myodegenerative processes associated with WB condition, we speculate that the higher pHu of WB meat might be the outcome of a drastically impaired energy-generating pathway combined with a deficiency and/or a dysfunction of muscle ATPases, having consequences also on muscle fibers contraction degree.